Community Adaptation towards the Shrinking of Lake Chad Basin, Borno State North East Nigeria - Dogo, A. N.; Ibrahim, M. H.; Abba, Chi Azimi, J. M.; Ahmad, F. A.; M. Ismail, Mohamad Ihsan (International Journal of Psychosocial Rehabilitation, 2020)
This study was to assess the community adaptation towards shrinking of Lake Chad Basin Borno State, north east Nigeria. The objectives were to: investigate the evidences of climate change in the communities of Lake Chad Basin Borno State, assess the communities challenges due to climate changes, recommend possible solutions to the problems associated with the effects of climate changes in the affected communities; Data for the study were obtained from both primary and secondary sources, secondary data were obtained from meteorology station and trend analysis of time series was done to examine the evidences of climate changes in the study area, while primary data was sourced through the administration of guided questionnaires to 252 respondents in the study area and human responses were analysed by Descriptive statistics of simple percentages, while bar charts were used to investigate and assessed the several community’s measures against the effects of climate change to water resources in the communities of Lake Chad Basin, Borno State North East Nigeria. Few Possible recommendations were also made for the future.